Reward-related neural correlates of early life stress in school-aged children. (June 2021) - Morelli, Nicholas M.; Liuzzi, Michael T.; Duong, Jacqueline B.; Kryza-Lacombe, Maria; Chad-Friedman, Emma; Villodas, Miguel T.; Dougherty, Lea R.; Wiggins, Jillian Lee
Highlights: Early life stress is associated with aberrant neural function. Altered neural function is apparent as young as early school age. Reward- and emotion-related regions show exaggerated activation/connectivity. Findings remain when controlling for concurrent stressful life events. Abstract: Objectives: Early life stress likely contributes to dysfunction in neural reward processing systems. However, studies to date have focused almost exclusively on adolescents and adults, measured early life stress retrospectively, and have often failed to control for concurrent levels of stress. The current study examined the contribution of prospectively measured cumulative life stress in preschool-age children on reward-related neural activation and connectivity in school-age children. Methods: Children ( N  = 46) and caregivers reported children's exposure to early life stress between birth and preschool age (mean = 4.8 years, SD  = 0.80). At follow-up (mean age = 7.52 years, SD = .78), participants performed a child-friendly monetary incentive delay task during functional magnetic resonance imaging. Results: Children with higher levels of cumulative early life stress, controlling for concurrent stressful life events, exhibited aberrant patterns of neural activation and connectivity in reward- and emotion-related regions (e.g., prefrontal cortex, temporal pole, culmen), depending on the presence of a potential reward and whether or not the target was hit or missed. Conclusions: Findings suggest that stress exposure during early childhood may impact neural reward processing systems earlier in development than has previously been demonstrated. Understanding how early life stress relates to alterations in reward processing could guide earlier, more mechanistic interventions.